Scanning tunneling microscopic and field emission microscopic studies of nanostructured molybdenum film synthesized by electron cyclotron resonance plasma - Purohit, Vishwas S.; Bhise, Ashok B.; Dey, Shirshendu; More, Mahendra A.; Dharmadhikari, C. V.; Joag, Dilip S.; Pasricha, Renu; Bhoraskar, S. V. (Vacuum, 2008)
Cathodic sputtering is demonstrated to be effective in synthesizing thin films of molybdenum nanoparticles. An electron cyclotron resonance plasma reactor has been used as the source. The particle size distribution is found to be controllable by proper choice of the cathodic bias potential. Sizes ranging between 20 and 30 nm deposited at the optimum bias potential are found to exhibit a self assembled structure as observed by scanning tunneling microscopy. Field emission microscopic studies on these films supported on W have exhibited very stable emission current over a period of 3 h. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: ECR plasma; Field emission microscopy; Hollow cathode chemical sputtering; Mo nanoparticles; Scanning tunneling microscopy

Synthesis of Cu-ZnO and C-ZnO nanoneedle arrays on zinc foil by low temperature oxidation route: effect of buffer layers on growth, optical and field emission properties - Jamali-Sheini, Farid; Patil, K. R.; Joag, Dilip S.; More, Mahendra A. (Applied Surface Science, 2011)
Different densities of ZnO nanoneedle films have been prepared by pre-coated zinc foils with thin layer of copper and carbon followed by thermal oxidation at 400 degrees C in air. The X-ray diffraction patterns show well defined peaks, which could be indexed to the wurtzite hexagonal phase of ZnO. The scanning electron microscope images clearly reveal formation of ZnO needles on the entire substrate surface. The X-ray photoelectron spectroscopy studies indicate that Cu and C ions are incorporated into the ZnO lattice. Photoluminescence studies evaluate different emission bands originated from different defect mechanism. From the field emission studies, the threshold field, required to draw emission current density of similar to 100 mu A/cm(2), is observed to be 2.25 V/mu m and 1.57 V/mu m for annealed zinc foil pre-coated with copper and carbon, respectively. The annealed film with copper layer exhibits good emission current stability at the pre-set value of similar to 100 mu A over a duration of 4 h. The results show that buffer layer is an important factor to control the growth rate, resulting in different density of ZnO needles, which leads to field emission properties. This method may have potential in fabrication of electron sources for high current density applications. (C) 2011 Elsevier B. V. All rights reserved.
Keywords: Buffer layer; Carbon; Copper; field emission; Nanoneedle; ZnO

Synthesis of single crystalline CdS nanocombs and their application in photo-sensitive field emission switches - Chavan, Padmakar G.; Badadhe, Satish S.; Mulla, Imtiaz S.; More, Mahendra A.; Joag, Dilip S. (Nanoscale, 2011)
Single crystalline CdS nanocombs were synthesized by a thermal evaporation route. The photo-sensitive field emission current shows a reproducible switching behavior, with a rise in current level of nearly five times the initial preset value of similar to 1 mu A. An ultra low turn-on field, required to draw an emission current density of similar to 0.1 mu A cm(-2) (100 nA), is found to be similar to 0.26 V mu m(-1) (260 V), which is much lower than the reported values for various other CdS nanostructures. Upon illumination with visible light the CdS nanocombs act as a photo field emission switch. At an applied field of similar to 0.65 V mu m(-1) the current densities are observed to be similar to 14.6 mu A cm(-2) and similar to 26.9 mu A cm(-2), without and with light illumination, respectively. The average emission current is seen to be stable over the duration of measurement for two preset values. The high sensitivity and fast response in the visible range indicates that the CdS nanocombs can be used as a photo-sensitive field emitting switch in device applications, and also in pulsed electron beam technology.

Superior field emission properties of layered WS2-RGO nanocomposites - Rout, Chandra Sekhar; Joshi, Padmashree D.; Kashid, Ranjit V.; Joag, Dilip S.; More, Mahendra A.; Simbeck, Adam J.; Washington, Morris; Nayak, Saroj K.; Late, Dattatray J. (Scientific Reports, 2013)
We report here the field emission studies of a layered WS2-RGO composite at the base pressure of similar to 1 x 10(-8) mbar. The turn on field required to draw a field emission current density of 1 mu A/cm(2) is found to be 3.5, 2.3 and 2 V/mu m for WS2, RGO and the WS2-RGO composite respectively. The enhanced field emission behavior observed for the WS2-RGO nanocomposite is attributed to a high field enhancement factor of 2978, which is associated with the surface protrusions of the single-to-few layer thick sheets of the nanocomposite. The highest current density of similar to 800 mu A/cm(2) is drawn at an applied field of 4.1 V/mu m from a few layers of the WS2-RGO nanocomposite. Furthermore, first-principles density functional calculations suggest that the enhanced field emission may also be due to an overalp of the electronic structures of WS2 and RGO, where graphene-like states are dumped in the region of the WS2 fundamental gap.

Spectral analysis of the emission current noise exhibited by few layer WS2 nanosheets emitter - Suryawanshi, Sachin R.; Kolhe, Pankaj S.; Rout, Chandra S.; Late, Dattatray J.; More, Mahendra A. (Ultramicroscopy, 2015)
Spectral analysis of the field emission (FE) current fluctuations has been carried out at the base pressure similar to 1 x 10(-8) mbar. The emission current stability investigated at preset value of 2 mu A is characterized by `step like fluctuation. The spectral analysis performed on a FFT (Fast Fourier Transform) analyzer revealed that the observed noise is of 1/f(alpha) type, with the value of alpha as similar to 1.05. The estimated value of alpha implies that the current fluctuations are mainly due the various processes occurring on atomic scale like adsorption, migration, and/or desorption of the residual gas species on the emitter surface. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Current fluctuations; field emission; Noise; WS2 nanosheets

Stable field emission from layered MoS2 nanosheets in high vacuum and observation of 1/f noise - Kashid, Ranjit V.; Joag, Pracheetee D.; Thripuranthaka, M.; Rout, Chandra S.; Late, Dattatray J.; More, Mahendra A. (Nanomaterials and Nanotechnology, 2015)
Field emission and current noise of hydrothermally synthesized MoS2 nanosheets are investigated in ultra-high-vacuum and industrially suited high-vacuum conditions. The study reveals that the emission turn-on field is pressure dependent. Moreover, the MoS2 nanosheets exhibit more stable field-electron emission in high-vacuum than in ultra-high-vacuum conditions. The investigations on field-emission current fluctuations show features of 1/f-type noise in ultra-high-vacuum and high-vacuum conditions, attributed to adsorption and desorption processes. The post-field-emission results indicate the MoS2 nanosheets are a robust field emitter in high-vacuum conditions.
Keywords: Electron emission; layered materials; MoS2; Noise measurement; Raman spectroscopy

Synthesis of GdB6 nanostructures using nanosecond (Nd: YAG) laser: field emission investigation - Suryawanshi, S. R.; Late, Dattatray J.; More, Mahendra A.; Singh, Anil K.; Sinha, S. (2015 28th International Vacuum Nanoelectronics Conference (IVNC), 2015)
We herein report field emission characteristics of GdB6 nanostructures grown directly on a pellet via laser processing (laser fluence similar to 6 J/cm(2)). The laser processed GdB6 pellet was characterized by X-ray diffraction, which revealed no change in phase upon laser processing. The values of the turn-on field required to draw emission current density of 1 mu A/cm(2) is found to be similar to 2.95 V/mu m, for the laser processed GdB6 emitter. Furthermore, the Fowler-Nordheim (F-N) plot exhibits non-linear behavior over the entire range of applied field and the field enhancement factor (beta) calculated from slope of the F-N plot (low field region) was found to be similar to 543. The emission current stability over a period of 3h was observed to be fairly good. The observed results demonstrate that laser processing can be efficiently used to make GdB6 nanostructure emitter having potential for practical applications.

Spatially branched CdS-Bi2S3 heteroarchitecture: single step hydrothermal synthesis approach with enhanced field emission performance and highly responsive broadband photodetection - Bankar, Prashant K.; Pawar, Mahendra S.; Pawbake, Amit S.; Warule, Sambhaji S.; Late, Dattatray J.; More, Mahendra A. (RSC Advances, 2016)
This report explores the controlled hierarchical synthesis of CdS nanostructure branches on Bi2S3 nanorod cores via a facile single step hydrothermal route. Morphological and structural studies reveal the formation of CdS-Bi2S3 heteroarchitecture with excellent stoichiometry between the constituent elements. The growth of CdS over Bi2S3 strongly depends on optimization of the reaction conditions, especially low PVP concentration. Furthermore, the as-synthesized CdS-Bi2S3 heteroarchitecture demonstrates multifunctionality in field emission and photoresponse. Interestingly, the CdS-Bi2S3 heteroarchitecture shows enhanced field emission properties such as low turn-on field (similar to 1.8 V mu m(-1) for 10 mu A cm(2)), high emission current density and better current stability in comparison to Bi2S3 and other nanostructures. The as-synthesized CdS-Bi2S3 heteroarchitecture exhibits considerable response and recovery times, similar to 207 ms and 315 ms, respectively in comparison to bare Bi2S3 nanostructures (similar to 655 ms and 678 ms). The present results demonstrate CdS-Bi2S3 heteroarchitecture as a potential candidate for future optoelectronic device applications.

Surface modification of aligned CdO nanosheets and their enhanced field emission properties - Bagal, Vivekanand S.; Patil, Girish P.; Deore, Amol B.; Suryawanshi, Sachin R.; Late, Dattatray J.; More, Mahendra A.; Chavan, Padmakar G. (RSC Advances, 2016)
Porous aligned CdO nanosheets were grown on a cadmium (Cd) substrate by the simple and cost effective method of thermal annealing. Further, decoration of gold (Au) nanoparticles on the porous aligned CdO nanosheets (specimen A) was achieved by coating with a Au thin film and subsequent annealing treatment. The average diameters of decorated Au nanoparticles were found to be 15 nm, 21 nm and 28 nm for the Au thin films with 20 s, 40 s and 60 s (specimens B, C, and D) coating times. Detailed characterizations, such as structural and morphological analysis of porous CdO nanosheets and Au/CdO nanocomposite (Au decorated porous CdO nanosheets), have been carried out using a Field Emission Scanning Electron Microscope (FESEM), X-ray diffraction (XRD) and a Transmission Electron Microscope (TEM). Field emission studies of specimens A, B, C and D were carried out in the planar diode configuration. Turn-on fields of 1.9 V mu m(-1), 1.1 V mu m(-1), 2.4 V mu m(-1) and 2.8 V mu m(-1) have been found for the emission current density of 10 RA cm(-2) for specimens A, B, C and D, respectively. The observed low turn -on field of specimen B (Au diameter of 15 nm) was found to be superior to other semiconducting nanostructures reported in the literature. The field emission current stability over a period of 3 h at the preset current density of 1 RA cm(-2) is found to be excellent for all specimens. To the best of our knowledge, field emission studies along with surface modification of porous aligned CdO nanosheets have not been reported in the literature. The simple synthesis route, facile surface modification and the superior field emission results make the present emitter very suitable for micro/nano electronic devices.

Synthesis, microstructure, optical and field emission studies of iron vanadium oxide nanosheets - Badadhe, Satish S.; Suryawanshi, Sachin R.; Naphade, Rounak A.; Chaudhary, Minakshi V.; More, Mahendra A.; Shelke, Manjusha V.; Ogale, Satishchandra B. (Journal of Physics D-Applied Physics, 2016)
We report a single step growth of thin graphene-like, densely packed FeV3O8 (FVO) nanosheets on silicon substrates via facile hydrothermal synthesis. These nanosheets have dimensions of a few microns with thin edges, offering very high aspect ratio. These FVO nanosheets exhibit excellent field emission behaviour with low turn on and threshold voltages of 1.3 V mu m(-1) and 1.7 V mu m(-1), respectively. The corresponding emitter delivers high emission current density of (similar to 1.650 mA cm(-2)) at fairly low applied field (similar to 4.00 V mu m(-1)).
Keywords: FeV3O8; field emission; nanosheets

Synthesis of Ni-doped ZnO nanostructures by low-temperature wet chemical method and their enhanced field emission properties - Rana, Amit Kumar; Bankar, Prashant; Kumar, Yogendra; More, Mahendra A.; Late, Dattatray J.; Shirage, Parasharam M. (RSC Advances, 2016)
In this study, we report an enhancement in the field emission (FE) properties of ZnO nanostructures obtained by doping with Ni at a base pressure of similar to 1 x 10(-8) mbar, which were grown by a simple wet chemical process. The ZnO nanostructures exhibited a single-crystalline wurtzite structure up to a Ni doping level of 10%. FESEM showed a change in the morphology of the nanostructures from thick nanoneedles to nanoflakes via thin nanorods with an increase in the Ni doping level in ZnO. The turn-on field required to generate a field emission (FE) current density of 1 mu A cm(-2) was found to be 2.5, 2.3, 1.8 and 1.7 V mu mcm(-2) for ZnO (Ni0%), ZnO (Ni5%), ZnO (Ni7.5%) and ZnO (Ni10%), respectively. A maximum current density of similar to 872 mu A cm(-2) was achievable, which was generated at an applied field of 3.1 V mu m cm(-2) for a Ni doping level of 10% in ZnO. Long-term operational current stability was recorded at a preset value of 5 mA for a duration of 3 h and was found to be very high. The experimental results indicate that Ni-doped ZnO-based field emitters can open up many opportunities for their potential use as an electron source in flat panel displays, transmission electron microscopy, and the generation of X-rays. Thus, the simple low-temperature (similar to 80 degrees C) wet chemical synthesis approach and the robust nature of the ZnO nanostructure field emitter can provide prospects for the future development of cost-effective electron sources.